RESPON INVESTOR DI SEKTOR PERTAMBANGAN TERHADAP PENGUMUMAN PSAK NO. 64: AKTIVITAS EKSPLORASI DAN EVALUASI PADA PERTAMBANGAN SUMBER DAYA MINERAL - Jessica Apriliani Koharyanto; yulius Jogi Christiawan (Business Accounting Review, 2016)
In 2011, the Indonesian Institute of Accountants (IAI) issued PSAK No. 64: Activities on Mining Exploration and Evaluation of Mineral Resources. When PSAK No. 64 was announced, investors analyzing the affect of PSAK No. 64 to the company’s financial statements and responding to the announcement of the PSAK. This study aimed to investigate the response of investors to the announcement of PSAK No. 64. The investor response was measured by using abnormal return, and to measure abnormal return this study using a market model. This study examined mining companies which in 2011 had shares in the Indonesia Stock Exchange. The results of this study found that investors did not respond to the announcement of PSAK No. 64.